Generational Differences in Adoption and Use of Information and Communications Technology. (September 2015) - Lee, Chaiwoo; Coughlin, Joseph F.
The increase in adoption and use of information and communications technology (ICT) by older adults calls for a more detailed understanding of their perceptions, experiences and decisions. Based on responses from a large-scale survey, this study investigates older adults' adoption and use of two ICT examples – mobile phones and PCs. Detailed open-ended responses from a national sample are quantitatively coded and analyzed with frequency analysis. The results of this study suggest that older adults' decisions on adoption and use of ICT are affected by multiple factors, including assessment of value, relevance with past experiences, compatibility with lifestyle, and affordability. Furthermore, findings from a comparative analysis suggest that perceived importance and effects of various adoption factors are different between generations, as well as between technology types and between stages of adoption – purchase, initial use and continued use. A summary of research and design implications is presented along with a discussion of the results.